Dark secrets of phytomelatonin. (6th May 2022) - Chen, Qi; Hou, Suying; Pu, Xiaojun; Li, Xiaomin; Li, Rongrong; Yang, Qian; Wang, Xinjia; Guan, Miao; Rengel, Zed
Abstract : Phytomelatonin works during nighttime by regulating circadian stomatal closure and growth of hypocotyl and shoot. Phytomelatonin impairs flavonoid biosynthesis and delays flowering time under non-stress conditions. Abstract: Phytomelatonin is a newly identified plant hormone, and its primary functions in plant growth and development remain relatively poorly appraised. Phytomelatonin is a master regulator of reactive oxygen species (ROS) signaling and acts as a darkness signal in circadian stomatal closure. Plants exhibit at least three interrelated patterns of interaction between phytomelatonin and ROS production. Exogenous melatonin can induce flavonoid biosynthesis, which might be required for maintenance of antioxidant capacity under stress, after harvest, and in leaf senescence conditions. However, several genetic studies have provided direct evidence that phytomelatonin plays a negative role in the biosynthesis of flavonoids under non-stress conditions. Phytomelatonin delays flowering time in both dicot and monocot plants, probably via its receptor PMTR1 and interactions with the gibberellin, strigolactone, and ROS signaling pathways. Furthermore, phytomelatonin signaling also functions in hypocotyl and shoot growth in skotomorphogenesis and ultraviolet B (UV-B) exposure; the G protein α-subunit (Arabidopsis GPA1 and rice RGA1) and constitutive photomorphogenic1 (COP1) are important signal components during this process. Taken together, these findings indicate that phytomelatonin acts as a darkness signal with important regulatory roles in circadian stomatal closure, flavonoid biosynthesis, flowering, and hypocotyl and shoot growth.